1988
DOI: 10.1007/bf02540689
|View full text |Cite
|
Sign up to set email alerts
|

Double bond oxidation of unsaturated fatty acids

Abstract: Different oxidizing agents for performing the cleavage oxidation of the double bond of the unsaturated fatty acids are presented, and their economic performance is analyzed. Ozone and sodium hypochlorite are the most commercially efficient oxidants.Laboratory work for the oxidation of oleic acid to azelaic and pelargonic acids using hypochlorite as oxidant is described. The advantages of working in an emulsion system and using RuC,13 as a catalyst are discussed, and a possible mechanism of the reaction is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 4 publications
(2 reference statements)
0
26
0
Order By: Relevance
“…4). This was inspired by classical methods of extraction [21], previously used for separation of dicarboxylic from monocarboxylic acids [22], and also applied in the specific case of the azelaic and pelargonic couple [23].…”
Section: Oxidative Cleavage In a Single Step (B)mentioning
confidence: 99%
“…4). This was inspired by classical methods of extraction [21], previously used for separation of dicarboxylic from monocarboxylic acids [22], and also applied in the specific case of the azelaic and pelargonic couple [23].…”
Section: Oxidative Cleavage In a Single Step (B)mentioning
confidence: 99%
“…[1][2][3] This conversion is nowadays mostly performed with second-and third-row transition-metal catalysts based on Os, [4][5][6][7][8][9][10][11][12] Ru, [13][14][15][16][17][18] or W, [19][20][21][22][23][24][25] on the lab scale, or with ozone in an industrial process. [3,26] More benign methods for these processes are clearly desired. Recently, we reported on the nonmetal-mediated oxidative cleavage of internal alkenes and unsaturated fatty acids into carboxylic acids with a combination of the oxidants oxone and sodium periodate.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of oleic acid in neutral oil in water emulsion resulted in the formation of dihydroxy, ketohydroxy, and diketo acids along with azelaic and pelargonic acids. Zaldman et al (11) used sodium hypochlorite as an oxidizing agent for the oxidation of oleic acid. The results showed that oxidation of oleic acid in an emulsion system consisting of sodium hypochlorite, surface-active agents, and ruthenium chloride as catalysts could be achieved with higher conversion and reduced reaction time compared with the nonemulsified (heterogeneous) systems.…”
mentioning
confidence: 99%